Organizing a Victory: A Review Essay on the BJP's 2014 Electoral Success. (December 2019) - Singh, Rajkamal; Goel, Garima
Suhas Palshikar, Sanjay Kumar and Sanjay Lodha (Eds.), Electoral Politics in India: The Resurgence of the Bharatiya Janata Party . London and New York: Routledge. 2017. 312 pages. ₹995. Ashutosh Kumar and Yatindra Singh Sisodia (Eds.), How India Votes: A State-by-State Look . New Delhi: Orient BlackSwan. 2019. 443 pages. ₹1395. Prashant Jha, How the BJP Wins: Inside India's Greatest Election Machine . New Delhi: Juggernaut Books. 2017. 235 pages. ₹399. Rajdeep Sardesai, '2014: The Election that Changed India' . Gurgaon: Penguin Books India. 378 pages. ₹399.